Pengembangan Media Scrapbook Berbasis Budaya Lokal untuk Meningkatkan Hasil Belajar IPAS pada Materi Keragaman Budaya - Kinanti, Putri; Akrom, Akrom; Meiliawati, Fithri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
The aim of this research is to develop local culture-based scrapbook media on cultural diversity material and to find out whether this media is feasible and can improve student learning outcomes. The method used in the research is R&D (Research and Development) with Thiagarajan's 4D model, which has four stages: define, design, develop, and disseminate. Data collection techniques used were observation, interviews, questionnaires, pre-test and post-test sheets. The product was tested in class IV with 18 students. Based on the research results, local culture-based scrapbook media has an average validation value from the three experts, namely 92% in the